Microbiological Isolation of Sporothrix Schenckii in an Immunocompromised Patient. A Case Report - Ledys Pérez Morales; Midiala Iglesias López; Odette Quiñones Cherta; Idalmis Reyes Rodríguez (Medisur)
Sporotrichosis is a subcutaneous mycosis with a variable course caused by a fungus of the genus Sporothrix. We present the case of 67-year-old white patient of rural origin with a history of myelofibrosis that had evolved for ten years and was treated with thalidomide and prednisone. He was admitted to the University General Hospital of Cienfuegos in August 2013 because of skin lesions on the left cheek, chest and forearms. During his stay in the Hematology ward due to his underlying disease, we consulted with the specialists of the Dermatology Department. Several diagnoses were established and multiple antimicrobial treatments were prescribed. No clinical improvement of the lesions was observed. A mycological study showed the presence of Sporothrix schencckii; hence, the patient underwent treatment for sporotrichosis. Given the rarity of this diagnosis in our institution, we decided to present this case.